2004
DOI: 10.1007/bf02504771
|View full text |Cite
|
Sign up to set email alerts
|

Shall we dance? A design epistemology for organizational learning and performance

Abstract: Management experts claim that organizational learning, knowledge management, intellectual capital, and related concepts are more important to today's organizations than traditional assets such as natural resources and skilled labor. Management thus enters domains more typically studied by those in training, education, and human performance technology, and fundamental questions asked by philosophers are now asked by CEOs; for example, What is knowledge? and How do people learn? Cook and Brown (1999) responded w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 35 publications
0
23
0
1
Order By: Relevance
“…Students in this study reported that it is not possible to see the consequences of their design judgments in hypothetical projects, especially when there is limited feedback from the instructor with no client or real learner involved. The importance of authentic learning experiences for students under the guidance of experts has been emphasized by many ID scholars (Ertmer & Cennamo, 1995 ;Quinn, 1994Quinn, , 1995Rowland, 2004 ;Tripp, 1994 ).…”
Section: Addressing Design Judgmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Students in this study reported that it is not possible to see the consequences of their design judgments in hypothetical projects, especially when there is limited feedback from the instructor with no client or real learner involved. The importance of authentic learning experiences for students under the guidance of experts has been emphasized by many ID scholars (Ertmer & Cennamo, 1995 ;Quinn, 1994Quinn, , 1995Rowland, 2004 ;Tripp, 1994 ).…”
Section: Addressing Design Judgmentmentioning
confidence: 99%
“…In addition, expert modeling has been suggested by several scholars to better prepare student designers for real-world instructional design (Cennamo & Holmes, 2001 ;Rowland, 2004 ;Rowland et al, 1992 ). Findings from this study reveal that modeling by practicing designers can help develop design judgment in novice designers because they learn more about real-world experiences and challenges, and practicing designers can bring to the classroom another viewpoint in addition to what students learn from their instructors.…”
Section: Addressing Design Judgmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Group creative design requires intentional choreography of the interplay between knowledge and learning (Cook and Brown 1999;Rowland 2004) Use structured design exercises to intentionally approach the problem in multiple ways.…”
Section: Practical Strategymentioning
confidence: 99%
“…Most importantly, such an approach brings into account an ''evolutionary consciousness", recognizing and embracing the role of the human in shaping and creating our future, in art as in life (Rowland, 2004). In this way, one may argue that all areas of design research could benefit from a physical, socio-cultural focus, acknowledging the reciprocal relationship of the physical world informing the digital, even as new technologies allow us (humans) to be shaped by them.…”
Section: Introductionmentioning
confidence: 99%